Village fund cash credit direct assistance recipient decision support system using the Simple Multi Attribute Rating Technique (SMART) method - Harmayani, Harmayani; Asti, Ardian; Apdilah, Dicky (Sinkron : jurnal dan penelitian teknik informatika, 2022)
Cash Direct Assistance is a program from the government due to the covid-19 pandemic conditions where with this Cash Direct Assistance is expected to be able to help restore the economy of people affected by government policies to stay at home and maintain their respective health. In determining the recipients of this assistance, the smallest government, namely the village government, still uses manual selection according to the criteria so that it requires a lot of time and high accuracy and a sophisticated application program is needed to overcome it. So in the design of the BLT Dana Desa application, the author designed using the PHP programming language with a decision-making system based on the SMART method where this application system was designed based on changing the processing system in the manual assessment of the recipient's family who was directly selected, now the author changes the assessment system for prospective recipients of cash direct assistance based on an application where this application will facilitate the determination of eligible families get assistance through a government program, namely direct cash assistance for village funds.